Efektivitas Kebijakan Perencanaan Pembangunan Kawasan Royal Baroe terhadap Pertumbuhan Ekonomi Lokal - Amealiea Prihatiningsih Malandy’s; Laeli Nur Khanifah; Siti Nurlita; Yolanda Mazmuria Manurung; Ria Amelia (Asosiasi Peneliti dan Pengajar Ilmu Hukum Indonesia, 2026)
One way for local governments to boost the local economy and improve urban planning is through area development. Using Rose’s theory of past, present, and future planning dimensions, this study aims to evaluate the effectiveness of the Royal Baroe Area development planning policy in promoting local economic growth in the city of Serang. This study employs a case study approach and collects data through observation, interviews, documentation, and a review of relevant literature. The results indicate that, in the past, the development of Royal Baroe was hindered by urban planning issues, the disorganization of the commercial district, and the need for a new economic growth center in Serang City. However, in the present, the district’s development has successfully improved the quality of public spaces, enhanced the district’s image, and created opportunities for community economic activities. Since the increase in visitor numbers has not yet fully correlated with increased business revenue, the economic impact felt by MSME operators remains suboptimal. To enhance Royal Baroe’s role as a hub for economic activity and a public space, the government has planned for the area’s sustainable development, integrated with the surrounding regions. However, to achieve long-term success, it is necessary to strengthen sustainable management plans, empower MSMEs, and promote the area. According to this study, the physical revitalization and urban planning of the Royal Baroe area are quite effective in driving sustainable local economic growth. However, more inclusive policies focused on community economic empowerment are still needed to optimize these efforts.